2014
DOI: 10.1155/2014/418694
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy with FOLFOX4 Regimen to Treat Advanced Gastric Cancer Improves Survival without Increasing Adverse Events: A Retrospective Cohort Study from a Chinese Center

Abstract: Background/Aim. To evaluate the clinical efficacy of FOLFOX4 (5-fluomumcil/leucovorin combined and oxaliplatin) neoadjuvant chemotherapy for advanced gastric cancer (AGC). Patients and Methods. Fifty-eight AGC patients were enrolled in this retrospective cohort study, 23 in the neoadjuvant group and 35 in the adjuvant group. R0 resection, survival, and adverse events were compared. Results. The two groups were well-matched, with no significant differences in R0 resection rate (82.6% versus 82.0%) and number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 29 publications
3
15
3
1
Order By: Relevance
“…Nine [ 9 , 17 – 22 , 24 , 25 ] out of eleven studies (5 RCTs and 4 CCTs) evaluated provided effective data for the calculation of the HR for OS. Compared with the AC group, the PC group had significantly better prognosis (HR, 0.74; 95 % CI, 0.61 to 0.89; P < 0.01, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nine [ 9 , 17 – 22 , 24 , 25 ] out of eleven studies (5 RCTs and 4 CCTs) evaluated provided effective data for the calculation of the HR for OS. Compared with the AC group, the PC group had significantly better prognosis (HR, 0.74; 95 % CI, 0.61 to 0.89; P < 0.01, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nine [ 9 , 17 – 22 , 24 , 25 ], nine [ 9 , 17 – 22 , 24 , 25 ], seven [ 9 , 17 , 18 , 20 – 22 , 25 ], six [ 9 , 18 , 20 , 21 , 23 , 25 ] studies reported 1-, 2-, 3-, 5- year survival rates, respectively. There were no significant differences in the 1- and 2-year survival rates between the two study groups (1-year survival rate: RR, 0.81; 95 % CI, 0.60 to 1.09; P = 0.17, Additional file 2 A; 2-year survival rate: RR, 0.90; 95 % CI, 0.77 to 1.04; P = 0.15, Additional file 2 B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Z. Sun з колегами у схожому дослідженні виявили, що проведення НАХТ за схемою FOLFOX 4 (лейковорин, 5-флуороурацил, оксаліплатин) значно підвищує показники виживаності пацієнтів із РШ на ранніх стадіях [20]. Так, у групі НАХТ загальна 3-річна виживаність становила 73,9%, у групі АХТ -40%, медіана загальної виживаності -29 та 22 міс відповідно (р=0,013).…”
unclassified